2020
DOI: 10.3390/su12208291
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Business Performance in Takaful Agencies: The Moderating Role of Objective Environment

Abstract: The previous research on the relationship between corporate social responsibility (CSR) and business performance produced mixed findings. Scholars exerted the mixed findings are largely influenced by several factors and contexts where different markets, type of companies, industries, and countries would show different results. On that basis, this study examines how the dimensions of objective environment influence the relationship between CSR dimensions and the business performance of Takaful agencies in Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Similarly, Hsiu-Jen and Shu-Yi (2014) find a significantly positive effect of CSR on companies' financial performance (ROA, ROE and EPS) in Taiwan. Nazri et al (2020) examine the relationship between CSR and business performance in the context of Takaful. They find that Takaful insurance should implement CSR activities to make firms successful worldwide.…”
Section: Corporate Social Responsibility and Takaful Performancementioning
confidence: 99%
“…Similarly, Hsiu-Jen and Shu-Yi (2014) find a significantly positive effect of CSR on companies' financial performance (ROA, ROE and EPS) in Taiwan. Nazri et al (2020) examine the relationship between CSR and business performance in the context of Takaful. They find that Takaful insurance should implement CSR activities to make firms successful worldwide.…”
Section: Corporate Social Responsibility and Takaful Performancementioning
confidence: 99%
“…The existing research on CSR highlights environment features as an important factor to consider when setting a particular CSR strategy (Achi et al, 2022;Nazri et al, 2020;Sun and Cui, 2014;Zhang et al, 2021). Managers should thus pay attention to such features, and in particular, to dynamism, when they design the firm's strategy in terms of CSR (Achi et al, 2022;Zhang et al, 2021).…”
Section: Environmental Dynamism and Corporate Social Responsibilitymentioning
confidence: 99%
“…Similarly, Hsiu-Jen and Shu-Yi (2014) found a signi cantly positive effect of CSR on companies' nancial performance (ROA, ROE, and EPS) in Taiwan. Nazri et al (2020) examine the relationship between CSR and business performance in the context of Takaful. They found that Takaful insurance should implement CSR activities to make the rm successful worldwide.…”
Section: Corporate Social Responsibility (Csr) and Performancementioning
confidence: 99%